Perlocutionary Act in Look Away Movie Script: Andra sari - Andra Sari; Fina Amalia Masri; Neil Amstrong (Program Studi Sastra Inggris Fakultas Ilmu Budaya Universitas Halu Oleo, 2022)
This research discussed how the perlocutionary act is used in the â€œLook Awayâ€ movie script. The objective of this research is to describe the functions of the perlocutionary act of the utterances of the characters in the â€œLook Awayâ€ movie script. This research uses a descriptive qualitative method and the data source of this research is taken from the â€œLook awayâ€ movie script. In this research, there are many data belonging to type two where the content of type two is that what the speaker said is not understood by the listener, usually causing a misunderstanding discourse. But there are also some data belonging to types one; what is the speaker said is understood by the speaker, types three; what is the speakerâ€™s intention was fully or partially understood by the listener, however, the listener did not work in that way, and types four; what is the speakerâ€™s intention was not been understood by the listeners, however, due to the involvement of other attendants in the communication, the speakerâ€™s expected perlocutionary act came true. This research also has similarities between the four types of perlocutionary acts by Qiang (2013) and perlocutionary act and communication and non-linguistic signs in the perlocutionary act in the book â€œOn Perlocutionary Actâ€ by Qiang (2013).